2007
DOI: 10.1111/j.1754-4505.2007.tb00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of adults with Down syndrome in Hong Kong

Abstract: The aim of this survey was to study the oral health status of Hong Kong Chinese adults with Down syndrome (DS). Sixty-five community-dwelling adults with DS (aged 17 to 42 years, 26.8+/-6.4) and age- and gender-matched controls attending a dental hospital were included in a cross-sectional survey. The subjects with DS had fewer filled (2.4+/-4.6 vs. 2.7+/-3.1, p=0.017) and fewer decayed (1.1 2.5 vs. 1.7+/-2.4, p=0.007) teeth than the control subjects. Significantly more peg-shaped maxillary lateral incisors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 26 publications
2
58
0
4
Order By: Relevance
“…Recently, it has been shown that a different salivary environment of electrolytes and pH is manifested in DS children, leading to the lower reported caries rate (Davidovich et al, 2010) 3.2 Periodontal disease DS individuals usually present with poor oral hygiene and manifested as marginal gingival inflammation, acute and subacute necrotizing gingivitis, advanced chronic periodontitis, loss of attachment in form of gingival recession and increased pocket depth, alveolar bone loss, suppuration or even abscesses, furcation involvement in the molars, increased tooth mobility, and even loss of teeth (Shaw & Saxby, 1986) (Figures 5B & 6). DS individuals had a prevalence of 60 to 90% percent and increased severity of periodontal disease compared with normal age-matched controls and subjects with other mental disabilities of similar age (Cutress, 1971b;Orner, 1976;Barnett et al, 1986;Reuland-Bosma & van Dijk, 1986;, Modeer et al, 1990;Shapira et al, 1991;Ulseth et al, 1991;Desai, 1997;Gabre et al, 2001;Lopez-Perez et al, 2002;Sakellari et al, 2005;Cheng et al, 2007;Khocht et al, 2010). Obviously the severity of periodontal disease among DS individuals is milder in recent years' reports as better dental care have been employed to take care of them early in their life.…”
Section: Dental Cariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that a different salivary environment of electrolytes and pH is manifested in DS children, leading to the lower reported caries rate (Davidovich et al, 2010) 3.2 Periodontal disease DS individuals usually present with poor oral hygiene and manifested as marginal gingival inflammation, acute and subacute necrotizing gingivitis, advanced chronic periodontitis, loss of attachment in form of gingival recession and increased pocket depth, alveolar bone loss, suppuration or even abscesses, furcation involvement in the molars, increased tooth mobility, and even loss of teeth (Shaw & Saxby, 1986) (Figures 5B & 6). DS individuals had a prevalence of 60 to 90% percent and increased severity of periodontal disease compared with normal age-matched controls and subjects with other mental disabilities of similar age (Cutress, 1971b;Orner, 1976;Barnett et al, 1986;Reuland-Bosma & van Dijk, 1986;, Modeer et al, 1990;Shapira et al, 1991;Ulseth et al, 1991;Desai, 1997;Gabre et al, 2001;Lopez-Perez et al, 2002;Sakellari et al, 2005;Cheng et al, 2007;Khocht et al, 2010). Obviously the severity of periodontal disease among DS individuals is milder in recent years' reports as better dental care have been employed to take care of them early in their life.…”
Section: Dental Cariesmentioning
confidence: 99%
“…Low prevalence of dental caries or tooth decay in both primary and permanent dentitions of DS individuals has been widely reported (Cutress, 1971a;Orner, 1975;Barnett et al, 1986;Vigild, 1986;Ulseth et al, 1991;Gabre et al, 2001;Bradley & McAlister, 2004;Cheng et al, 2007;Dellavia et al, 2009;Davidovich et al, 2010). Cutress (1971a) examined 416 DS subjects and found lower prevalence of dental caries than normal population, but after adjusting the age of teeth eruption, there were only small and no significant difference between 2 groups.…”
Section: Dental Cariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of periodontal disease is almost 100% occurring in patients with trisomy 21 under 30-year old. Although plaque, calculus and local irritant are present and oral hygiene is poor the severity of periodontal destruction exceeds that explainable by local factors alone (Cichen et al, 1998;Cheng et al, 2011). Cutler et al, in study for two brothers with acute necrotizing ulcerative gingivitis concluded that two factors have been proposed to explain the high prevalence and increase severity of periodontal destruction in trisomy 21 associated with reduced resistance to infections because of gingival poor circulation (Cutler et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of gingivitis is very high among this group of patients, due to high vascularization of gingival tissue. In his study of adult Chinese with trisomy 21, Cheng concluded that adults with DS had poorer periodontal health than similar age-and gender-matched control subjects (Cheng et al, 2011) Modifiable risk factors that play a great role in causation and progression of chronic oral diseases are prevalent among children with learning disabilities. The environmental and host factors had been documented as associated factors with periodontal diseases and dental caries in children with trisomy 21.…”
Section: Introductionmentioning
confidence: 99%